2007
DOI: 10.1093/hmg/ddm364
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the PTEN promoter by statins and SREBP

Abstract: Germline mutations in the tumor-suppressor gene PTEN predispose to heritable breast cancer. The transcription factor peroxisome proliferator-activated receptor-gamma (PPARgamma) has also been implicated as a tumor suppressor pertinent to a range of neoplasias, including breast cancer. We previously demonstrated that lovastatin may signal through PPARgamma and directly upregulate PTEN expression at the transcriptional level. In our current study, we show that simvastatin, pravastatin and fluvastatin can induce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 35 publications
2
34
0
Order By: Relevance
“…Reporter constructs included a full-length (À1344 to À1) and truncated (À1344 to À1001) PTEN promoter (Teresi et al, 2008). Both PTEN promoters, the full-length as well as the À1344 to À1001 segments, could be inhibited by DHT and activated by Casodex in AR-positive LNCaP and C4-2 cells (Figure 1c).…”
Section: Ar-mediated Pten Transcriptional Repression In Prostate Cancmentioning
confidence: 99%
See 1 more Smart Citation
“…Reporter constructs included a full-length (À1344 to À1) and truncated (À1344 to À1001) PTEN promoter (Teresi et al, 2008). Both PTEN promoters, the full-length as well as the À1344 to À1001 segments, could be inhibited by DHT and activated by Casodex in AR-positive LNCaP and C4-2 cells (Figure 1c).…”
Section: Ar-mediated Pten Transcriptional Repression In Prostate Cancmentioning
confidence: 99%
“…We generated PTEN promoters tagged with the firefly luciferase gene, as described in our previous study (Teresi et al, 2008). Reporter gene activity was determined by dual luciferase assay using a luciferase enzyme assay system (Promega, Madison, WI, USA).…”
Section: Western Blottingmentioning
confidence: 99%
“…Several studies have implicated phophoinositide 3-kinase (PI3K), protein kinase B (Akt), and endothelial nitric oxide synthase (eNOS) upregulation in the mechanism of cardioprotection [reviewed in Ludman et al (30)], which is consistent with the notion that signaling through Akt and mammalian target of rapamycin (mTOR) is generally regarded as a prosurvival pathway. In contrast, others have reported that acute statin administration upregulates phosphatase and tensin homolog (PTEN), which would antagonize the Akt/mTOR signaling pathway (11,54). PTEN does so by dephosphorylating phosphatidylinositol (3,4,5)-triphosphate (PIP 3 ), effectively blunting Akt activation.…”
mentioning
confidence: 99%
“…65 This builds on a very interesting connection between statin-induced increases in PTEN transcription via a sterol response element-binding protein (SREBP) pathway. 66 PTEN is a component in cell cycle regulation and inhibits transduction of the insulin signal by converting phosphatidylinositol (3,4,5)-trisphosphate (PIP 3 ) back to PIP 2 ( Fig. 1), preventing activation of phosphoinositide-dependent kinase-1 (PDK1) and subsequent phosphorylation of AKT.…”
Section: Future Directions: Downstream Of the Inflammasomementioning
confidence: 99%